The Elohist: a seventh-century theological tradition - Gnuse, Robert Karl (Cascade Books, 2017)
Introduction -- Scholarly research on the Elohist -- Critics of the Elohist and my response -- Prophetic narratives in Samuel and Kings -- The social and theological setting of the Elohist -- Theology of the Elohist -- Commentary on Elohist texts -- The modern relevance of the Elohist -- Conclusion